BERTRAND de MUÑOZ, Maryse: Si me quieres escribir. Canciones políticas y de combate de la guerra de España. Madrid: Calambur, 2009 - Rodríguez Jiménez, Francisco Javier (Studia Historica. Historia Contemporánea, 2011)
Reseña